THE ANALYSIS OF AGRICULTURE LEADING SECTOR AGAINST ECONOMIC GROWTH IN BOGOR REGENCY OF WEST JAVA PROVINCE - Ruhiyat, Endang; Rusdi, Rusdi; Rima Prasetya, Eka (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2018)
This study pupose to analysis the leading sectors of agriculture in Bogor Regency, Analyzing the specialization of agricultural growth in Bogor Regency, Analyzing Growth of Superior Sectors in Bogor Regency. Method of analysis using Location Quotient, Regional Specialization and Shift Share. The results of this study indicate that agriculture superior sector in Bogor Regency is food crops subsector, plantation crops, livestock and its products, forestry, fishery. While the Growth Specialization of Agriculture Sector shows that there is no Specialization of Growth of Agricultural Sector in Bogor Regency to West Java Province. Then based on the Shift Share results show There is an economic sector in Bogor regency grew faster than the average provincial growth of the Sub Sector of food crops that is 2,162,177,188, then Livestock subsector and the results that have the second highest value of 1,236,933,539, and most The sector in Bogor Regency is relatively developed, the name of agriculture sub-sector is relatively less developed, only the fishery sub-sector has a rapid development of 179,655,562 for the agricultural sector, Bogor Regency has a less good competitiveness, especially the plantation sub-sector is very strong In regional share